Efektivitas Undang-Undang Nomor 16 Tahun 2019 Terhadap Pernikahan Di Bawah Umur - Aulil Amri; Muhadi Khalidi (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
Legal certainty and firmness must exist in a law or regulation. Because without legal certainty, the rights of legal subjects will be taken away and neglected. Likewise, without strictness in the law, it will make legal subjects feel worried and insecure because they feel that the law does not provide protection for them. Law Number 16 Year 2019 concerning Amendments to Law Number 1 Year 1974 is deemed not to have legal certainty and firmness, because the stipulation of the age limit for marriage in this law only considers and is based on Law Number 35 Year 2014 concerning Amendments to Law Number 23 Year 2002 Concerning Child Protection. Furthermore, Law Number 16 Year 2019 still provides an opportunity for the Indonesian people to carry out child marriage. Law Number 16 Year 2019 must look at various other legal aspects and have clear legal consequences, so a comprehensive revision of this law is required. Even if possible, Law Number 1 Year 1974 must be reviewed and adjusted to the current and future legal problems. By applying the concept of benefit and rejecting harm in a law or regulation, the objectives of the law or regulation will be achieved and become effective.